ALKALINE PRETREATMENT DAN PROSES SIMULTAN SAKARIFIKASI-FERMENTASI TERHADAP KADAR ETANOL DARI SERABUT KELAPA - Era Devi Istihaji; Joko Budiarto; Lisa Mastura; Rianthy Juniar; Muhammad Cahyo; Dedy Irawan (2477 - 6165, 2017)
This mature coconut fibers utilized have traditionally been handcrafted with low economic value and mostly just be a waste. In this study, coconut fibers used as materials for bioethanol. A total of 100 grams of fibers delignified by using NaOH solution with a concentration variation of 1%, 1.5%, 2%, 2.5% and 3%, which was created earlier. Delignification carried out for 90 minutes at a temperature of 90°C and the stirring rotation of 150 rpm. Then the results of delignification rinsed and fibers are fermented for 7 days simultaneously using 15% Saccharomyses cerevisiae, Trichoderma sp 10% and 5% Aspergillus niger. Fermented then filtered and distilled liquid to be taken. The results were analyzed using GC distillation and obtained the best results with ethanol concentration of 213.12 mg / mL and the resulting yield of 2.69%.